Ответ:
Объяснение:
A) (a+b)(c+3)= ac +3a +bc + 3b
б) (2x+y)(3-3z) = 6x -6z + 3y -3yz
в) (a-2b)(3x-4y) =3ax - 4ay - 6bx + 8by
г) (m+n)(a-b+1) = ma - mb + m + na - nb + n
д) (a+b-2)(c+5) = ac +5a + bc + 5b - 2c - 10
e) (2x-y-1)(a-3b) = 2xa -6xb -ya +3yb -a + 3b
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
A) (a+b)(c+3)= ac +3a +bc + 3b
б) (2x+y)(3-3z) = 6x -6z + 3y -3yz
в) (a-2b)(3x-4y) =3ax - 4ay - 6bx + 8by
г) (m+n)(a-b+1) = ma - mb + m + na - nb + n
д) (a+b-2)(c+5) = ac +5a + bc + 5b - 2c - 10
e) (2x-y-1)(a-3b) = 2xa -6xb -ya +3yb -a + 3b